Substance Use Behaviors and Perceived Stress Among Resident Registered Nurse Anesthetists. - Jaworowski, Daniel; Klinowski, Joey; Szulc, Marta; Wakefield, Meaghan (AANA Journal, 2026)
One in four clinicians who seek treatment for substance use disorder are anesthesia providers. However, there is a dearth of research on substance use behaviors of doctoral resident registered nurse anesthetists (RRNA). The purpose of this study was to determine the prevalence and patterns of substance use and perceived stress levels among RRNAs. Anonymous surveys were distributed to RRNAs enrolled in doctoral programs in the United States. Respondents self-reported four substance use behaviors. Problematic substance use and perceived stress were self-reported using the Drug Abuse Screening Test (DAST-10) and the Perceived Stress Scale (PSS-10). Overall, 26.5% of respondents reported engaging in nonprescription substance use behaviors since enrollment. The prevalence of anesthetic agent use was 7.4%. Nine percent of respondents reported use of focus-enhancing drugs, 15% reported increased alcohol consumption, and 22% required a new prescription since enrollment. Mean PSS-10 scores were significantly higher in respondents who reported substance use behaviors (19.8 [SD, 6.5] vs 16.5 [SD, 6.3] P < 0.001). Predictive factors for substance use include enrollment period greater than 24 months, male gender, and elevated PSS-10 and DAST-10 scores.